2020
DOI: 10.1016/j.heliyon.2020.e03175
|View full text |Cite
|
Sign up to set email alerts
|

Altered microtubule structure, hemichannel localization and beating activity in cardiomyocytes expressing pathologic nuclear lamin A/C

Abstract: Given the clinical effect of laminopathies, understanding lamin mechanical properties will benefit the treatment of heart failure. Here we report a mechano-dynamic study of LMNA mutations in neonatal rat ventricular myocytes (NRVM) using single cell spectroscopy with Atomic Force Microscopy (AFM) and measured changes in beating force, frequency and contractile amplitude of selected mutant-expressing cells within cell clusters. Furthermore, since beat-to-beat variations can provide clues on the origin of arrhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder resulting from loss-of-function of dystrophin [ 64 ]. In skeletal and cardiac myocytes cells, dystrophin is a membrane-associated protein that links the cytoskeleton and the surrounding extracellular matrix, thereby providing mechanical integrity during muscle cell work [ 65 ].…”
Section: Connexin43 and Myocardial Pathologymentioning
confidence: 99%
“…Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder resulting from loss-of-function of dystrophin [ 64 ]. In skeletal and cardiac myocytes cells, dystrophin is a membrane-associated protein that links the cytoskeleton and the surrounding extracellular matrix, thereby providing mechanical integrity during muscle cell work [ 65 ].…”
Section: Connexin43 and Myocardial Pathologymentioning
confidence: 99%
“…In 2015, Lanzicher et al investigated the biomechanical impact of LMNA missense mutations in neonatal rat ventricular myocytes (NRVM), and found damages on the actin cytoskeleton, suggesting loss of actin filament anchorage by dysfunction of the laminar proteins at the nuclear membrane as the initiating alteration [7,8]. Their results were further confirmed by different studies, in which it was demonstrated that lamina network mutations induce an alteration of actin filaments, microtubule, and intermediate filament anchorage in the nuclear membrane, a region critical for cytoskeleton organization [9,10]. Moreover, the link between the lamina network and the cytoskeleton filaments is ensured by a protein complex: LInker of Nucleoskeleton and Cytoskeleton (LINC).…”
Section: Introductionmentioning
confidence: 80%
“…Finally, other mechanisms may be implicated in the defective mechanotransduction of LMNA mutant cardiac cells. In cardiomyocytes with three different LMNA missense mutations, we previously reported defective adhesion, altered actin, and microtubule networks and dislocated connexin 43 [10] leading to higher frequency of beating but with a reduced beating force. However, future studies should investigate the complex molecular changes in LMNA mutant cardiac fibroblasts.…”
Section: Study Limitationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Impairment of the microtubule network triggered abnormal electrical communication between cardiomyocytes and induced cardiac conduction defects in Lmna H222P / H222P , Lmna N195K / N195K and Lmna Δ 8–11 /Δ 8–11 mice [ 95 , 96 , 97 ]. Increased phosphorylation and aberrant localization of Cx43 have been reported, in vivo and in vitro, due to microtubule instability [ 96 , 97 , 98 ]. Stabilization of microtubules using paclitaxel, a microtubule-stabilization agent commonly used in chemotherapy, improved intraventricular conduction defects in Lmna H222P / H222P mice, demonstrating a novel pathophysiological mechanism based on microtubule network and Cx43 displacement [ 97 ].…”
Section: Therapies For Striated Muscle Laminopathiesmentioning
confidence: 99%